Pelarangan Terhadap Makanan Halal Perspektif Maqāṣidu Al-Syarī’ah (Studi Tentang Imbauan Asrama Putri Stiba Makassar): Prohibition On Halal Food From The Perspective Of Maqāṣidu Al-Syarī’ah (A Study Of The Appeal Of The Stiba Makassar Girl's Dorm) - Sartini Lambajo; Rosmita; Nurhayati Abubakar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study aims to determine the perspective of maqāṣidu al-Syarī’ah on the prohibition of halal food in the STIBA Makassar Girls' Dormitory. The problems that the author raises in this study are; First, how is the concept of prohibition of halal food seen from maqāṣidu al-Syarī’ah. Second, how is the application of maqāṣidu al-Syarī’ah in the context of the appeal to prohibit halal food in the STIBA Makassar Girls' Dormitory. This study uses a type of field research using a normative and phenomenological approach. The results of the research found are as follows; First, the concept of prohibition of halal food in Islam can be seen from several factors that influence it. The most important factor is fulfilling the criteria of halal and ṭayyib. The term halal refers to the type of food that is not forbidden and is permitted to be consumed. Halal means sought, obtained, and collected not in a haram way. Meanwhile, ṭayyib refers to food that provides benefits, goodness, and well-being. The term ṭayyib in food refers to something that provides benefits to the body. Second, the application of Maqāṣidu al-Syarī'ah in the context of the appeal to prohibit halal food in the STIBA Makassar female dormitory can be seen from 5 main elements: protecting religion, soul, mind, lineage, and wealth. This appeal aims to ensure that female students consume healthy food so they can carry out religious activities properly, avoid diseases that can disrupt health, maintain the strength and intelligence of female students' thinking power, prevent negative impacts that will affect the health of reproductive organs such as menstrual disorders, and minimize the level of wastefulness.